Confidence and career choices: An experiment - Kai Barron; Christina Gravert (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Confidence is often seen as the key to success. Empirical evidence about how such beliefs about one's abilities causally map into actions is, however, sparse. In this paper, we experimentally investigate the causal effect of an increase in confidence about one's own ability on two central choices made by workers in the labor market: choosing between jobs with different incentive schemes, and the subsequent choice of how much effort to exert within the job. An exogenous increase in confidence leads to an increase in subjects' propensity to choose payment schemes that depend heavily on ability. This is detrimental for low ability workers. Policy implications are discussed.
Keywords: C91; D03; M50; J24; 330; Overconfidence; experiment; beliefs; real-effort; career choices